Early Excision and Grafting versus Delayed Skin Grafting in Burns Covering Less than 15% of Total Body Surface Area; A Non- Randomized Clinical Trial - Mehdi Ayaz; Hamid Bahadoran; Peyman Arasteh; Abdolkhalegh Keshavarzi (Bulletin of Emergency and Trauma, 2014)
Objective: To compare outcome of patients with burns covering less than 15% of total body surface area(TBSA) undergoing early excision and grafting or delayed skin grafting. Method: This was a non-randomized clinical trial including 54 patients with less than 15% TBSA burn referring to Ghotboddin Hospital of Shiraz. They were assigned to two study groups, each group including 27 patients: the early excision and grafting group (EEG group) and the delayed grafting group (DG group). Patients were followed postoperatively for 6 months. Hospital stay, graft success rate, itching score and scar formation during 6 months of follow-up were recorded and compared between two study groups. Results: During the study 1 patient was lost to follow-up in early excision and grafting group. Baseline characteristics were comparable between two study groups. The graft success rate was significantly higher in those patients who underwent early excision and grafting when compared to delayed grafting group (96.88% vs. 92.88%; p=0.033). However the length of hospital stay, itching and scar scores were comparable between two study groups after 6 months of follow-up. Conclusion: In patients with burns covering less than 15% TBSA, early excision and grafting is associated with higher graft success rates compared to the delayed excision and grafting. How ever length of hospital stay, itching and scar formation is comparable between the two techniques. Clinical Trial Registry: This trial is registered with the Iranian Clinical Trial Registry (IRCT2013092313880N2).